Low Density Lipoprotein Receptor Variants in the Beta-Propeller Subdomain and Their Functional Impact - Dušková, Lucie; Nohelová, Lucie; Loja, Tomáš; Fialová, Jana; Zapletalová, Petra; Réblová, Kamila; Tichý, Lukáš; Freiberger, Tomáš; Fajkusová, Lenka (Frontiers in Genetics, 2020)
Background: Pathogenic variants in the low density lipoprotein receptor gene are associated with familial hypercholesterolemia. Some of these variants can result in incorrect folding of the LDLR protein, which is then accumulated inside the cell and cannot fulfil its function to internalize LDL particles. We analyzed the functional impact of 10 LDLR variants localized in the beta-propeller of epidermal growth factor precursor homology domain. The experimental part of the work was complemented by a structural analysis on the basis of 3D LDLR protein structure. Methods: T-Rex Chinese hamster ovary cells transfected with the human LDLR gene were used for live cell imaging microscopy, flow cytometry, and qRT-PCR analysis. Results: Our results showed that the analyzed LDLR protein variants can be divided into 3 groups. (1) The variants buried inside the 3D protein structure expressing proteins accumulated in the endoplasmic reticulum (ER) with no or reduced plasma membrane localization and LDL particle internalization, and associated with an increased gene expression of ER-resident chaperones. (2) The variants localized on the surface of 3D protein structure with slightly reduced LDLR plasma membrane localization and LDL particle internalization, and associated with no increased mRNA level of ER-resident chaperones. (3) The variants localized on the surface of the 3D protein structure but expressing proteins with cell responses similar to the group 1. Conclusions: All analyzed LDLR variants have been evaluated as pathogenic but with different effects on protein localization and function, and expression of genes associated with ER stress.